Organizational Diagnosis and Assessment: Bridging Theory and Practice - Bélanger, Laurent (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "Organizational Diagnosis and Assessment: Bridging Theory and Practice," by Michael I. Harrisson and Arie Shirom.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Management; Organizational change; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z